Time in Office and the Changing Gender Gap in Dishonesty: Evidence from Local Politics in India - Ananish Chaudhuri; Vegard Iversen; Francesca R. Jensenius; Pushkar Maitra (Center for Economic Studies and ifo Institute (CESifo), 2020)
Increasing the share of women in politics is regularly promoted as a means of reducing corruption. In this paper, we look for evidence of a gender gap in dishonesty among elected representatives, as well as how this changes with time in office. Based on a sample of 356 inexperienced and experienced local politicians in West Bengal, India, we combine survey data on attitudes towards corruption with data from incentivized experiments. While we find little evidence of a gender gap in the attitudes of inexperienced politicians, a lower faith in political institutions and a greater distaste for corruption can be seen among experienced politicians, particularly women. However, this seeming hardening in attitudes among female politicians also coincides with more dishonest behavior in our experiments. Exploring mechanisms for this difference, we find it to be strongly associated with lower risk aversion. Our study indicates that gender gaps in politics should be theorized as dynamic and changing, rather than static.
Keywords: H11; C93; 330; politicians; gender; honesty; die-tossing game; experiments